The Effect Of The Variable Of Tax Expense, Tunneling Incentive And Leverage On Transfer Pricing With Profitability As A Moderating Variable - Sulhendri Sulhendri; Sabaruddin Sabaruddin; Septi Wulandari Chairina (Fakultas Ekonomi Universitas Indonesia Timur, 2023)
This study aims to examine the effect of the variable of tax expense, tunneling incentive and leverage on transfer pricing with profitability as a moderating variable. This study is quantitative using secondary data obtained from manufacturing companies with food and beverage sector listed on the Indonesia Stocks Exchange (IDX) in 2015-2020. The sampling process used a purposive sampling technique using several criteria that have been determined by the researcher. The data analysis technique used is panel data analysis using the statistical application of E-Views 12 as a data tool. The results of this study indicate that tax expense, tunneling incentive and leverage on transfer pricing together affect transfer pricing. Partially, tax expense and leverage have a positive insignificants effect on transfer pricing. Tunneling incentive has a positive significants effect on transfer pricing. And then, profitability has a positive significant with tax expense on transfer pricing